Human Activities and Conservation Awareness between Community Use Zone (CUZ) Areas of Kinabalu Park and Crocker Range Park, Sabah - Andy R. Mojiol; Maureen J. Tapuang; Razak Wahab (UMK Publisher, 2016)
The Parks Enactment 1984 prohibits any human activities in the Park in order to conserve the natural ecosystem but in reality there are some people living inside the Park and doing cultivation. Community Use Zone (CUZ) is a management option in an attempt to strike a balance between the conservation priorities of the Park and the livelihoods of the local communities who depend on the Park for survival. This study looks into the relationship between types of crops planted within the CUZ areas, evaluate the contribution for the local communities’ livelihood, and determine the perception and conservation awareness of local community activities. The data for this study was collected by using face-to-face interview technique. Closed and open-ended structured questions were used in the interview. Apart from that observation was useful to obtained information which cannot achieve from structured interviews. Percentage, mean and range were used to summarize the results. With the use of socioeconomic survey and economic valuation on sales products approach, it was possible to determine the objectives of this study. Major crops grown are permanent crops such as rubber trees, fruit trees, and cash crops such as vegetables, cocoa and coffee trees were identified as the type of crops that were cultivated for economic sources by farmers in Kg. Sayap, Kota Belud and Kg. Mongool Baru Ulu Senagang, Keningau/Tenom. Rubber trees contributed the highest source of income followed by fruit trees such as durian, langsat and rambutan, cocoa trees and vegetables. The study showed that the perception and conservation awareness of the local communities in both villages had high awareness level. They are aware of the issues that concerning forest conservation. The study had determined that the CUZ is a tool management for the local communities to survive their living which is recommended to be applied but further research on the local communities’ livelihood dependency on protected areas should be conducted for the sake of forest conservation.